From farm to table: Agrifood systems and trade challenges in the Southern Cone - Piñeiro, Valeria; Piñeiro, Martín; Bianchi, Eduardo; Elverdin, Pablo; Illescas, Nelson; Papendieck, Sabine; Pascuzzi, Nieves; Rodriguez, Augustín Tejeda (International Food Policy Research Institute, 2023)
Food production includes a complex and varied set of agricultural and nonagricultural activities, involving a growing number of sectors and actors that influence the way food is produced, processed, distributed, and consumed. Recently, and especially after the 2021 United Nation Food Systems Summit (UNFSS), it has been proposed that this conglomerate of activities and socioeconomic actors be jointly identified as food systems. National food systems, which exist in each country, are interrelated through trade and other factors with regional food systems and finally with the global food system. The concept of food systems has been adopted as a useful tool for understanding the multiple and complex interrelations between different production, distribution, and trade partners and for adjusting policy analysis and design to this complex world. The discussions and documentation prepared during the UNFSS process brought to public attention not only the utility and complexity of this concept but also some of the shortcomings of current food production practices. The summit also highlighted an urgent need to establish processes for identifying such shortcomings, their relative importance, and possible measures that would lead to the transformation of national food systems and the global food system.